2001
DOI: 10.1067/mcp.2001.117937
|View full text |Cite
|
Sign up to set email alerts
|

Determination of in vivo absorption, metabolism, and transport of drugs by the human intestinal wall and liver with a novel perfusion technique

Abstract: First-pass metabolism by the intestinal wall is extensive and contributes to the same extent as the liver to low bioavailability of some drugs such as verapamil. Moreover, intestinal secretion is as important as biliary excretion for the elimination of metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
84
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 25 publications
4
84
1
Order By: Relevance
“…This was indeed one of the main limitations to use of ERMBT in the current study, although our results were similar in subjects carrying the CC genotype compared with those who did not (i.e. carrying the TT genotype).Although the total mass of CYP3A4 in the entire small intestine has been estimated to be around 1% of that in the liver, there is increasing evidence that intestinal CYP3A can contribute significantly, in some cases equally to hepatic CYP3A, to the overall first-pass metabolism of several drugs [43][44][45][46]. In addition, rifampicin has been shown to be capable of inducing intestinal CYP3A4 [47].…”
contrasting
confidence: 40%
See 1 more Smart Citation
“…This was indeed one of the main limitations to use of ERMBT in the current study, although our results were similar in subjects carrying the CC genotype compared with those who did not (i.e. carrying the TT genotype).Although the total mass of CYP3A4 in the entire small intestine has been estimated to be around 1% of that in the liver, there is increasing evidence that intestinal CYP3A can contribute significantly, in some cases equally to hepatic CYP3A, to the overall first-pass metabolism of several drugs [43][44][45][46]. In addition, rifampicin has been shown to be capable of inducing intestinal CYP3A4 [47].…”
contrasting
confidence: 40%
“…Although the total mass of CYP3A4 in the entire small intestine has been estimated to be around 1% of that in the liver, there is increasing evidence that intestinal CYP3A can contribute significantly, in some cases equally to hepatic CYP3A, to the overall first-pass metabolism of several drugs [43][44][45][46]. In addition, rifampicin has been shown to be capable of inducing intestinal CYP3A4 [47].…”
Section: Control Phasementioning
confidence: 99%
“…administration of VP (80 mg/kg) to healthy volunteers (Hashiguchi et al, 1996), corrected for the B/P ratio (Robinson and Mehvar, 1996), were 29 and 121 ng ⅐ h/ml, respectively, and the corresponding AUCs of the NVP enantiomers were 80 and 168 ng ⅐ h/ml. First-pass metabolism of VP in enterocytes has also been reported in humans (Sandström et al, 1999;von Richter et al, 2001). The extraction ratios of R-and S-VP by enterocytes were 0.49 and 0.68, respectively, and those by liver were 0.63 and 0.79, respectively (Sandström et al, 1999).…”
Section: Stereoselective First-pass Metabolism Of Verapamilmentioning
confidence: 88%
“…Although basic knowledge concerning human intestinal drug enzyme and transporter expression has been collected over the past decade (Obach et al, 2001;Thorn et al, 2005), the ultimate proof for their significance has been given by in vivo studies. For several compounds, such as cyclosporin, verapamil, and midazolam, in vivo studies have shown significant first-pass metabolism by the intestinal wall (Kolars et al, 1991;von Richter et al, 2001;Glaeser et al, 2004). The significance of the intestine in determining the faith of drugs within the body is not only expressed by its high capacity to metabolize drugs but also by its sensitivity to induction and inhibition of drug-metabolizing enzymes (Pelkonen et al, 2001), in addition to the interplay between transporters and metabolic activity (Suzuki and Sugiyama, 2000;Benet et al, 2004;Jeong et al, 2005).…”
mentioning
confidence: 99%
“…Although the liver has long been thought to play the major role in drug metabolism, the metabolic capacity of the intestine has been increasingly recognized (von Richter et al, 2001;Glaeser et al, 2004).…”
mentioning
confidence: 99%